The Architects’ And Landscape Architects’ Views On The Design And Planning Of The Hospital Courtyard Gardens (HCG) In Malaysia - Madihah Mat Idris; Magda Sibley; Karim Hadjri (Malaysian Institute of Planners, 2024)
Indexed by Scopus/MyCite